2017
DOI: 10.1111/dpr.12208
|View full text |Cite
|
Sign up to set email alerts
|

Engendering Growth Diagnostics: Examining Constraints to Private Investment and Entrepreneurship

Abstract: The growth constraints diagnostic is a framework that seeks to help countries identify ‘binding’ constraints to private investment and entrepreneurship. Curiously absent from the diagnoses of the 31 countries to which this framework has been applied is any mention of gender gaps. This is surprising given the substantial literature providing evidence that gender gaps in education, income, employment, resource control and access affect economic growth and well‐being. This article ‘engenders’ the standard growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Despite India's economic growth over the past few decades, the country continues to lag in achieving gender equality. Scholars and policy-makers see entrepreneurialism as a route to raising women's economic participation and socioeconomic status (Ghosh & Cheruvalath, 2007;Roncolato et al, 2017;World Bank, 2012). The trend in entrepreneurial initiatives since 2000 has focused on microcredit and financial support programmes.…”
Section: Women's Entrepreneurship In Indiamentioning
confidence: 99%
“…Despite India's economic growth over the past few decades, the country continues to lag in achieving gender equality. Scholars and policy-makers see entrepreneurialism as a route to raising women's economic participation and socioeconomic status (Ghosh & Cheruvalath, 2007;Roncolato et al, 2017;World Bank, 2012). The trend in entrepreneurial initiatives since 2000 has focused on microcredit and financial support programmes.…”
Section: Women's Entrepreneurship In Indiamentioning
confidence: 99%
“…This article has shown that criticisms of the classic HRV growth diagnostic, mostly raised by practising economists, have merit. Critics argue that the HRV diagnostic focuses too narrowly on capital accumulation as its objective, stresses the quantity rather than the quality of growth, and fails to disaggregate constraints across economic agents or space (Felipe et al, 2011; Ianchovichina & Lundstrom Gable, 2009; Martins, 2013; Roncolato et al, 2017; Sabates‐Wheeler, 2009; USAID, 2015).…”
Section: Conclusion and Policy Lessonsmentioning
confidence: 99%
“…Data limitations also restrict diagnostics. Roncolato et al (2017) have pointed out that there is a lack of data on constraints facing women, marginalized spheres of economic activity and issues of distribution. Hausmann et al (2008) concede that their diagnostics suffer from a data “availability bias” that leads to some constraints being more easily rejected or accepted.…”
Section: Conclusion and Policy Lessonsmentioning
confidence: 99%
See 2 more Smart Citations